A review of multisystem inflammatory syndrome in children (MIS-C) related to COVID-19 - Carlson Kurniawan (Intisari Sains Medis, 2022)
Global pandemic of Coronavirus Disease 2019 (COVID-19) caused by SARS-CoV-2, a novel virus which first reported in Wuhan in December 2019. It can cause severe respiratory conditions including respiratory failure. Different from adults, children usually have milder symptoms of the disease. A post-infection complication that involves multisystem organ failure in children is reported in numerous countries. It is mentioned as multisystem inflammatory syndrome in children (MIS-C) or Kawa-COVID-19, because it resembles Kawasaki Disease. The pathogenesis remains unclear, but it is presumed that hosts’ innate immune response triggered the condition. Modulating the immune response is the main target of the therapy. High doses of intravenous immunoglobulins, low doses of corticosteroids (methylprednisolone), anti-IL-1 (anakinra), antiplatelet such as aspirin can be used to treat MIS-C. Antiviral therapy is not proven to be effective and other immunomodulatory agents still needed further studies.